Assessment of CAD-CAM polymers for digitally fabricated complete dentures - Perea-Lowery L.; Minja I.K.; Lassila L.; Ramakrishnaiah R.; Vallittu P.K. (Mosby Inc., 2022)
Statement of problem
Information on the mechanical properties of the materials used for manufacturing computer-engineered complete dentures is scarce.
Purpose
The purpose of this in vitro study was to evaluate the mechanical properties of 3 prepolymerized polymethyl methacrylate (PMMA) resins used in the fabrication of computer-aided design and computer-aided manufacturing (CAD-CAM) milled complete dentures (CDs), as well as 2 denture base polymers used for conventionally fabricated CDs.
Material and methods
Three CAD-CAM materials were evaluated: Degos Dental L-Temp, IvoBase CAD, and Zirkonzahn Temp Basic Tissue. Two materials used for conventionally manufactured dentures were also included as controls (Palapress and Paladon 65). Each material type was sectioned into bars for flexural strength, nanohardness, elastic modulus, and surface microhardness evaluation (n=8/material). Half of the specimens were stored in water for 30 days, while the other half was dry-stored. A 2-way ANOVA was conducted to detect the effect of material and storage on the evaluated properties (α=.05). Linear contrasts were conducted to compare the differences among the 3 types of CAD-CAM material and the conventional ones.
Results
Material type and storage had a significant influence on the flexural strength, nanohardness, elastic modulus, and surface hardness of the materials investigated (P<.001). The post hoc Scheffé test for flexural strength revealed a nonsignificant difference in the interaction between Degos L-Temp and Paladon (P=1.000). In terms of nanohardness, no difference was found when comparing Palapress with Paladon, as well as IvoBase CAD with Zirkonzahn Temp Basic (P=1.000). A nonsignificant interaction in terms of surface hardness was also found between IvoBase CAD and Palapress (P=.575).
Conclusions
The tested materials showed variation in their mechanical properties, with satisfactory behavior of the CAD-CAM materials. However, the results obtained when testing the materials used for the conventional fabrication of complete dentures suggest that their use might still be advisable.